Proses Perencanaan, Perekrutan dan Penempatan SDI pada Pabrik Tahu Saudara Jaya - Nanda Anggun Kharisma; Deliani Faradillah; Anastasya Veronica Parera (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to analyze the process of planning, recruitment, and placement of Human Resources (HR) at Saudara Jaya Tofu Factory. The availability of quality HR is a crucial factor in supporting operational effectiveness and achieving organizational goals, especially in small-scale manufacturing industries such as tofu factories. The research methods used are in-depth interviews with owners/managers and key employees, and direct observation of daily activities related to HR management in the factory environment. The results of the study indicate that the HR planning process at Saudara Jaya Tofu Factory tends to be informal and based on immediate needs, not long-term projections. Recruitment is mostly done through recommendations from existing employees or word of mouth in the surrounding environment, with selection criteria that focus on work experience and willingness to learn. Employee placement is done flexibly, adjusting to daily production needs and observed individual abilities. Nevertheless, it was found that this informal approach was quite effective in meeting the operational needs of Saudara Jaya Tofu Factory, considering the relatively simple scale of the business and characteristics of the work.